Research on Operation Mechanism and Construction Path of Government Information Ecological Chain in Big Data Era - Wu, Wenya; Zhu, Simin; Yang, Chuanjie (Transactions on Computer Science and Intelligent Systems Research, 2024)
From "manual administration" to "information administration", the government constructs a new model of big data governance based on chain-dependent relations through the means of information technology and transmission and feedback of data information resources: Government Information Ecology Chain. It has the characteristics of information sharing, link diversity and information control, including the three components of node, chain and environment. Value-added mechanism, coordination and cooperation mechanism, dynamic balance mechanism is the operating mechanism of the government information ecological chain. The opening of government information, the self-organization ability of government information ecological chain and the ecological environment of government information affect the formation and development of the government information ecological chain. Therefore, it is necessary to build a government information ecological chain from fostering a scientific culture of government information ecological chain, enhancing the security of government information ecology chain, innovating the service mode of government information ecology chain, and building the platform of government information ecological chain.